Incidence and reasons for conversion of laparoscopic cholecystectomy to open cholecystectomy - Acharya, Arjun; Gurung, Narendra Vikram; Poudel, Suresh Raj (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Cholelithiasis is one of the most common problems affecting the gastrointestinal tract. The objective of the study was to find the incidence of cases converted to open cholecystectomy from laparoscopic cholecystectomy and find the association with other intra-operative and preoperative findings. Methods: This is a prospective observational study. One hundred elective laparoscopic cholecystectomy cases in the institution of the study were the study sample. Pre-operative and intra-operative findings were noted. Conversion in surgery from laparoscopic cholecystectomy to open cholecystectomy was also recorded and the association was tested through Fisher’s exact test. Results: The rate of conversion from laparoscopic cholecystectomy to open cholecystectomy was 5%. which was significantly related to sex, time duration of the surgery, bleeding, and anatomical difficulties. Conclusions: The conversion rate is only 5% which was significantly associated with sex, time duration of surgery, intraoperative bleeding, and anatomical difficulties.